Using the potential of the creative economy to restore Ukraine - Iryna Moiseienko (International Journal of Management and Economics, 2022)
The concept of the creative economy in the modern global world is filled with new meanings and acquires many qualitatively new features and properties. The article describes the development of creative economy models. A comparative analysis of the characteristics of the creative economy in EU countries and Ukraine was carried out. Through statistical analysis of creative activities in the economy of Ukraine, we determined the list of growth parameters. Using analysis of the studies on the creative economy in Ukraine, we determined the peculiarities and problems of its formation to formulate the principles and priorities of the state policy for the development of the creative economy in Ukraine. The modern model of the creative economy of Ukraine is proposed to be supplemented by the development of creative human potential.
Keywords: E61; O11; O20; O57; P51; 650; characteristics; creative economy; creative economy indicators in EU and Ukraine; model; state policy